2011
DOI: 10.4104/pcrj.2010.00079
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic assessment of patients with interstitial lung disease

Abstract: The diagnosis of interstitial lung disease (ILD) is frequently delayed because clinical clues are neglected and respiratory symptoms are ascribed to more common pulmonary diagnoses such as chronic obstructive pulmonary disease (COPD) in the primary care setting. While ILD cases ultimately require referral to a pulmonologist, general practitioners can play a crucial role in recognising the need for, and initiating, a diagnostic evaluation. An initial assessment hinges upon a structured history and physical exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…The relative lack of inflammation, high levels of hyperplastic type II alveolar cells, and subpleural localization of fibrosis in ILD (4,8,13) and the pump model (but not in the direct model) are striking and possibly interrelated observations. In another study (6) in which a single dose of intratracheal bleomycin was compared with multiple doses, it was concluded that the multiple-dose model was more similar to IPF because the multiple-dose model and IPF (but not the singledose model) showed relatively low levels of inflammation and high levels of hyperplastic type II alveolar cells.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The relative lack of inflammation, high levels of hyperplastic type II alveolar cells, and subpleural localization of fibrosis in ILD (4,8,13) and the pump model (but not in the direct model) are striking and possibly interrelated observations. In another study (6) in which a single dose of intratracheal bleomycin was compared with multiple doses, it was concluded that the multiple-dose model was more similar to IPF because the multiple-dose model and IPF (but not the singledose model) showed relatively low levels of inflammation and high levels of hyperplastic type II alveolar cells.…”
Section: Discussionmentioning
confidence: 95%
“…There are no treatments approved by the Food and Drug Administration for these diseases. The pathological changes associated with ILD result in impairment of lung gas exchange and loss of pulmonary function, leading to dyspnea, respiratory failure, and death (7,8,15,30).…”
mentioning
confidence: 99%
“…1 Because of their low incidence and non-specific symptoms, ILDs are difficult to recognise, and this may cause diagnostic delay. 2 We were very interested to read the review by Gulati on the diagnosis of ILDs published in the PCRJ last year, 3 in which he concluded that, "General practitioners can prevent diagnostic delays by recognising clinical clues, reviewing relevant exposures, and uncovering the presence of possible connective tissue disease, as well as ordering HRCT chest scans and pulmonary function tests if possible." However, the diagnostic pathway for ILDs in primary care has hardly been studied.…”
Section: Diagnostic Pathways For Interstitial Lung Diseases In Primarmentioning
confidence: 99%
“…This protects patients against undue, costly and potentially risky diagnostic tests, and may even reduce diagnostic delay caused by referral to the wrong specialist. As Gulati advises, 3 if symptoms persist and advanced diagnostic services are available, a GP can then order a non-invasive HRCT scan to identify an ILD, and refer as appropriate. As most ILDs are very rare, a definitive diagnosis by a GP is not feasible and referral to the appropriate specialist is warranted.…”
Section: Diagnostic Pathways For Interstitial Lung Diseases In Primarmentioning
confidence: 99%
“…Other common causes of death in patients with IPF therefore include acute coronary syndromes, congestive heart failure, lung cancer, and infectious causes. 7 Regrettably, late presentation often shortens the survival time of patients with IPF and there is often a delay of 1-2 years before presentation with symptoms and additionally there may be a problem with clinicians missing early clinical clues, 8 although this will not alter the natural course of the disease process.…”
mentioning
confidence: 99%